Mother's Knowledge Before and After Menopause Counseling - Ernawati, Ernawati; Sumarmi, Sumarmi; Nuryana, Riska; Kartini, Anita; Halim, Nuraeni Safitri (Bantayang Omni Cendekia, 2025)
Background: The menopausal transition, which includes the premenopausal phase and the cessation of menstruation, often leads to anxiety and unpreparedness among women due to hormonal changes. These changes result in various physical and psychological symptoms. Enhancing knowledge about menopause is essential for better coping and adaptation. Objective: To assess the level of maternal knowledge regarding menopause before and after a counseling intervention in Salajo Village, South Bontonompo District, Gowa Regency. Methods: This study employed a descriptive quantitative design using a one-group pretest-posttest approach. A total of 46 menopausal mothers participated through total sampling. Data were collected using a validated questionnaire and analyzed using descriptive statistics with SPSS version 25. Results: Before counseling, 39 out of 46 participants (84.8%) had good knowledge about menopause, while 7 participants (15.2%) had limited knowledge. After counseling, the number of respondents with good knowledge increased to 45 (97.8%), with only one participant (2.2%) remaining in the limited category. Conclusion: Counseling significantly improved maternal knowledge about menopause. The intervention proved effective in enhancing awareness of menopausal symptoms and phases. This underscores the importance of structured health education programs to empower women in managing the menopausal transition.